The analysis of antimicrobials epidemiological cut-off values of mycoplasma gallisepticum isolated from goose - Yangshuo Li; Jingyi Liang; Weihuo Li; Yixin Jia; Sheng Yuan; Yuanyuan Zhou; Yuee Hou; Nan Zhang (Poultry Science)
Mycoplasma gallisepticum (MG) poses a significant threat to the goose breeding industry, with antimicrobial agents commonly employed for its treatment. However, the absence of standardized criteria for antimicrobial selection complicates clinical decision-making regarding the choice and dosage of these agents, contributing to the emergence of clinical resistance. In this study, we isolated 102 clinical strains of MG from geese in Guangdong. We determined the minimum inhibitory concentration (MIC) values for various antimicrobials frequently used in MG treatment, including danofloxacin, enrofloxacin, tilmicosin, tylosin, tylvalosin, valnemulin, tiamulin, and spectinomycin. After conducting a statistical analysis of the susceptibility test results, we employed ECOFFinder to establish the wild-type cutoff values (ECOFFs) for these antimicrobials against the MG isolates. The findings revealed a significant reduction in sensitivity among the clinical isolates to the eight tested antimicrobial agents. While valnemulin and tiamulin maintained relatively good sensitivity, enrofloxacin, danofloxacin, and spectinomycin exhibited notably diminished effectiveness. The determined ECOFFs for MG isolated from geese against the aforementioned antimicrobials were 3.2, 3.2, 0.8, 0.8, 0.08, 0.05, 0.05, and 3.2 μg/mL, respectively. This study is crucial for identifying resistant strains and investigating resistance mechanisms, in addition to providing a precise assessment of the resistance levels of MG isolated from geese in Guangdong. The insights gained from this research will serve as a valuable reference for the prevention and treatment of MG infections and will promote more effective clinical strategies regarding the use of antimicrobials.